2016
DOI: 10.1111/mec.13680
|View full text |Cite
|
Sign up to set email alerts
|

Ericaceous plant–fungus network in a harsh alpine–subalpine environment

Abstract: In terrestrial ecosystems, plant species and diverse root-associated fungi form complex networks of host-symbiont associations. Recent studies have revealed that structures of those below-ground plant-fungus networks differ between arbuscular mycorrhizal and ectomycorrhizal symbioses. Nonetheless, we still remain ignorant of how ericaceous plant species, which dominate arctic and alpine tundra, constitute networks with their root-associated fungi. Based on a high-throughput DNA sequencing data set, we characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
94
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 90 publications
(220 reference statements)
8
94
0
Order By: Relevance
“…In general, DNA-barcoding-based analyses do not provide any direct evidences of niche differentiation or interspecific interactions [10, 42, 43]. Therefore, our aim was not revealing “common mycelial networks” linking fungal (and host plant) individuals/species [5, 44] but detecting sings of potential niche differentiation and interspecific interactions [42, 43]. Throughout this paper, we use the term “network” in a broad sense [38] irrespective of physical (mycelial) connections among fungi.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, DNA-barcoding-based analyses do not provide any direct evidences of niche differentiation or interspecific interactions [10, 42, 43]. Therefore, our aim was not revealing “common mycelial networks” linking fungal (and host plant) individuals/species [5, 44] but detecting sings of potential niche differentiation and interspecific interactions [42, 43]. Throughout this paper, we use the term “network” in a broad sense [38] irrespective of physical (mycelial) connections among fungi.…”
Section: Methodsmentioning
confidence: 99%
“…The 3,862,747 reads that passed the filtering processes were clustered with a cutoff sequence similarity of 97% in a parallelized process of the Minimus for accurate assembling/clustering [54] as implemented in Claident and the obtained consensus sequences were then used as operational taxonomic units (OTUs) in the following statistical analyses. In the clustering process, reads of each sample were clustered beforehand with a 98% cutoff similarity: the results of the within-sample dereplication was used as guide information in order only to accelerate the 97% clustering process [35, 43]. OTUs whose sequencing reads were less than ten in all the samples were removed because their sequences could contain PCR/sequencing errors [55].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ishida and Nordin (29) identified such host effects on ERM fungal communities in V. vitis-idaea and V. myrtillus in northern Sweden. Toju et al (56) reported significant host preferences in root-associated fungi in 3 out of 16 ericaceous plant species on Mt. Tateyama, Japan.…”
mentioning
confidence: 99%